1998
DOI: 10.1104/pp.118.2.683
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Photosynthesis to Elevated CO2under Low-Nitrogen Nutrition Is Affected by the Capacity for Assimilate Utilization. Perennial Ryegrass under Free-Air CO2 Enrichment

Abstract: Acclimation of photosynthesis to elevated CO 2 has previously been shown to be more pronounced when N supply is poor. Is this a direct effect of N or an indirect effect of N by limiting the development of sinks for photoassimilate? This question was tested by growing a perennial ryegrass (Lolium perenne) in the field under elevated (60 Pa) and current (36 Pa) partial pressures of CO 2 (pCO2) at low and high levels of N fertilization. Cutting of this herbage crop at 4-to 8-week intervals removed about 80% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
169
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 31 publications
8
169
0
2
Order By: Relevance
“…In a recent free-air CO 2 enrichment study of ryegrass, Rogers et al (1998) also observed that elevated [CO 2 ] leads to a marked decrease of Rubisco large subunit when the nitrogen supply was restricted, but not when more nitrogen fertlizer was supplied. In ryegrass, the decrease of Rubisco was associated with an increase of the leaf-sugar level, and both reverted after cutting to increase the sink-source ratio (Rogers et al 1998).…”
Section: Elevated [Co 2 ] Alters the Nitrogen Status Dramatically Whementioning
confidence: 92%
See 2 more Smart Citations
“…In a recent free-air CO 2 enrichment study of ryegrass, Rogers et al (1998) also observed that elevated [CO 2 ] leads to a marked decrease of Rubisco large subunit when the nitrogen supply was restricted, but not when more nitrogen fertlizer was supplied. In ryegrass, the decrease of Rubisco was associated with an increase of the leaf-sugar level, and both reverted after cutting to increase the sink-source ratio (Rogers et al 1998).…”
Section: Elevated [Co 2 ] Alters the Nitrogen Status Dramatically Whementioning
confidence: 92%
“…In ryegrass, the decrease of Rubisco was associated with an increase of the leaf-sugar level, and both reverted after cutting to increase the sink-source ratio (Rogers et al 1998). The different response of sugars in limiting nitrogen in rye grass and tobacco might be due to the larger amounts of starch synthesized in the latter.…”
Section: Elevated [Co 2 ] Alters the Nitrogen Status Dramatically Whementioning
confidence: 99%
See 1 more Smart Citation
“…The influence of elevated pCO 2 on NDP frequency was not as strong as hypothesised. It is possible that the 9 y exposure to elevated pCO 2 resulted in an acclimation of the soil-plant system to function under these conditions (Rogers et al, 1998). Previous experiments have shown that the type of nitrate reductase enzyme carried by the NDP differed under ambient and elevated pCO 2 (Roussel-Delif et al, in press), suggesting that NDP populations may respond to elevated pCO 2 by altering both the enzyme type, and probably its activity.…”
Section: Frequency Of Nitrate Dissimilating Pseudomonasmentioning
confidence: 98%
“…Consequently, the main influence is thought to occur by the intermediation of the plants. Indeed, because of the competitive inhibition by O 2 of the ribulose-1,5-bisphosphate carboxylase, which is responsible for CO 2 fixation during photosynthesis [7], the C 3 plant photosynthetic rate increases under a CO 2 -enriched atmosphere [28,47,51]. An increased root biomass under CO 2 enrichment has been shown by several authors [25,30,47,52,53].…”
Section: Introductionmentioning
confidence: 93%